Exposure–response analysis of efficacy and safety for pexidartinib in patients with tenosynovial giant cell tumor. (14th October 2021) - Yin, Ophelia; Zahir, Hamim; French, Jonathan; Polhamus, Daniel; Wang, Xiaoning; van de Sande, Michiel; Tap, William D.; Gelderblom, Hans; Wagner, Andrew J.; Healey, John H.; Greenberg, Jonathan; Shuster, Dale; et al.
Abstract: This analysis was conducted to assess exposure–response relationships for efficacy and safety of pexidartinib in patients with tenosynovial giant cell tumor. Efficacy was assessed categorically by overall response rate (ORR) with Response Evaluation Criteria in Solid Tumors version 1.1 and longitudinally (changes in tumor size and volume). Safety included hepatic parameters (i.e., alanine aminotransferase [ALT], aspartate aminotransferase [AST], and total bilirubin). Average pexidartinib concentration (Cavg ) was identified as the primary exposure parameter correlated with response. In categorical and longitudinal analyses, higher Cavg coincided with greater ORR and tumor size reduction, respectively, with smaller joint size having a greater impact. For safety, a significant relationship was observed between Cavg and incidence of ALT‐related and AST‐related adverse events (AEs). With increased exposure, an increase in efficacy was predicted with near maximum effect at 800 mg/day. Higher initial dose (1000 mg/day) during the first 2 weeks did not improve efficacy. Higher doses were associated with an increased risk of ALT‐related and AST‐related AEs. These results support the US Food and Drug Administration–approved dose (400 mg two times/day without initial loading dose).